Going for the wallet?: rule-of-law conditionality in the next EU multiannual financial framework - Heinemann, Friedrich (Intereconomics, 2018)
EU funds that promote economic convergence will hardly reach their objective in countries sliding toward a system that lacks effective checks and balances. The idea of financially sanctioning EU Member States has been advocated for some time and took shape concretely in May 2018. The European Commission presented a draft regulation to sanction Member States with “generalised deficiencies” in the rule of law, which was presented together with a comprehensive proposal for the next MFF.